Professores que ensinam Matemática nos anos iniciais do Ensino Fundamental: aprendizagens da docência em um grupo colaborativo - Tanaka, Ana Lúcia Freire (2015)
The research aimed to identify and analyze the learnings acquired by first grade teachers through collaborative actions shared in a group that was created from Programa Observatório da Educação/Capes/Inep (Observatory Program of Education/Capes/Inep). It is a project called Collaborative Network of Practices for Training Math Teachers: multiple views, dialogues and contexts. This program intends the creation of a collaborative network among distinct postgraduate programs: the postgraduate program in Education of Universidade Federal de São Carlos; three programs related to Education of Pontifícia Universidade Católica de São Paulo (Math Education, Education: Psychology of Education and Education: Training of trainers) and a program of Universidade Federal do ABC. The discussion of different learnings and knowledge that happened through the activities experienced by a collaborative/reflexive group is sought in this study. With the support of literature it was possible the comprehension of the different processes that occurred in the trajectory of the group composed by first grade math teachers, future teachers and postgraduate students of Education and Math Education. Using authors as Zeichner (2010), Imbernón (2009), Tancredi (2009), Marcelo García (1999), Cochran-Smith & Lytle (1993) Fiorentini (2006), Vaillant & Marcelo (2012) and Gatti & André (2010) and analyzing the obtained data it can be pointed out that the collaborative groups are able to assist to the several possibilities of the learning of the teachers. The movement of the group allowed to look at the experiences of the participants through the socialization of the successes and difficulties met at the moments of reflection of their practices and the written production of each one in which was found a process of re-meaning, not only of the trajectory with the contribution of the group, but also the strengthening of the professional choice of the participants